Financing the development of old waqf properties (New York)
xxvii, 267 sayfa
Keywords: “This book presents successful case studies in Muslim and Muslim minority countries that have revolutionized the redevelopment of idle waqf properties into productive land trusts. The revival of this institution over the last two decades shows the growing optimism in galvanizing the socioeconomic role of waqf by adopting its flexible shariah measures. Innovative ways of financing redevelopment allow Muslims to extend these roles to include new beneficiaries. New uses for these properties include providing services to the community, opening jobs for the majority of people, funding small entrepreneurs, educating the masses, providing health care, and sheltering the poor and needy. Countries under study include Sudan, Turkey, Malaysia, Indonesia, Singapore, New Zealand, Kuwait, Oman, Qatar, and Iran. Additionally, the book examines the International Development Bank's role in financing the development old waqf properties in different countries“ --